2023
DOI: 10.1007/s10900-023-01188-7
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Socio-demographic, Economic and Individual Reasons for COVID-19 Vaccination Hesitancy in Ecuador: A Nationwide Longitudinal Study

Abstract: The current outbreak of SARS-Cov-2, a virus responsible for COVID-19, has infected millions and caused a soaring death toll worldwide. Vaccination represents a powerful tool in our fight against the transmission of SARS-CoV-2. Ecuador is one of the Latin American countries most impacted by COVID-19. Despite free COVID-19 vaccines, Ecuadorians still hesitate to get vaccinated. A multivariate binary logistic regression was used to analyze data from the Ecuadorian National Institute of Statistics and Censuses. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…This shows the social, health, economic, and political vulnerability of indigenous, ethnic or minority populations during the pandemic, and the need to focus government actions on policies aimed at reducing such vulnerability [25] , [26] . At the same time, it has been observed that ethnic groups also present greater hesitancy to be vaccinated [27] , so health education and communication strategies are also necessary to reduce the inequalities observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This shows the social, health, economic, and political vulnerability of indigenous, ethnic or minority populations during the pandemic, and the need to focus government actions on policies aimed at reducing such vulnerability [25] , [26] . At the same time, it has been observed that ethnic groups also present greater hesitancy to be vaccinated [27] , so health education and communication strategies are also necessary to reduce the inequalities observed.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies also show the most economically disadvantaged sectors are less likely to be vaccinated against COVID-19 [32] , [33] . At the same time, those populations with greater economic disadvantages also presented greater hesitancy to vaccination [10] , [27] .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, socio-demographic factors at the individual level have been found to influence vaccine uptake (Reichmuth et al, 2023). However, existing studies often report conflicting associations and are often limited to specific population groups (Backhaus & Health, 2023;de Figueiredo, Simas, & Larson, 2023;Kabir et al, 2022;Lapo-Talledo, Talledo-Delgado, Portalanza, Ballaz, & Siteneski, 2023), making them less applicable for informing broader policy and program-making efforts. To address these gaps in knowledge, we conducted this study to identify the motivations behind COVID-19 vaccination uptake in Bangladesh and explore their associations with socio-demographic factors.…”
Section: Introductionmentioning
confidence: 99%